Use of Dalbergia palo-escrito as a vegetable alternative to rabbit tanned leather - Ortiz-Gutiérrez, Lina Johatzin; Soto-Simental, Sergio; Zepeda-Bastida, Armando; Ocampo-López, Juan; Ayala-Martínez, Maricela (Ecosistemas y Recursos Agropecuarios, 2021)
Evaluate the Dalbergia palo-escrito, as a natural tanning agent for rabbit skin. Two tests were carried out with extracts of D. palo-escrito, for the first, with leaf and stem, for the second the stem at different concentrations (20, 40 and 60 g L-1). With the extract, it carried out the tanning of rabbit skin, to evaluate color, texture and physical properties of the skin. The leaf and 60 g L-1 of stem extract decreased (P< 0.05) luminosity, while it did not affect the loss of weight and size of the skin. The loss of skin weight, firmness and fracturing increased with 40 g L-1; with 20, 40 and 60 g L-1 the loss of area and the proportion of size decreased, instead they increased softness, gloss and firmness. Concluded that the rabbit skins tanned with extracts of D. palo-escrito at a concentration of 40 g L-1, presented better physical quality.